Campomanesia lineatifolia Ruiz & Pavón (Myrtaceae): Isolation of major and minor compounds of phenolic-rich extract by high-speed countercurrent chromatography and anti-inflammatory evaluation. (28th June 2023) - Neves, Nívea Cristina Vieira; de Mello, Morgana Pinheiro; Zaidan, Isabella; Sousa, Lirlândia Pires; Braga, Alysson Vinícius; Machado, Renes Resende; Kukula-Koch, Wirginia; Boylan, Fabio; Caliari, Marcelo Vidigal; Castilho, Rachel Oliveira
Abstract: Ethnopharmacological relevance: Campomanesia lineatifolia Ruiz & Pavón (Myrtaceae), an edible species found in Brazilian Forest, possesses leaves that are traditionally used for the treatment of gastrointestinal disorders in Brazil. Extracts of C. lineatifolia are rich in phenolics and exhibit antioxidant, and gastric antiulcer properties. Furthermore, Campomanesia spp. have been described to possess anti-inflammatory properties, but studies related to chemical constituents of C. lineatifolia are scarce in the literature. Aim of the study: This work aims to identify the chemical composition of the phenolic-rich ethanol extract (PEE) from C. lineatifolia leaves and evaluate the anti-inflammatory activity that could be related to its ethnopharmacological use. Materials and methods: The high-speed countercurrent chromatography (HSCCC), using an isocratic and a step gradient elution method, and NMR, HPLC-ESI-QTOF-MS/MS were used to isolate and identify the chemicals of PEE, respectively. Lipopolysaccharide-(LPS)-stimulated THP-1 cells were used to evaluate the anti-inflammatory activities from PEE and the two majority flavonoids isolated by measure TNF-α and NF-κB inhibition assays. Results: Fourteen compounds were isolated from the PEE, further identified by NMR and HPLC-ESI-QTOF-MS/MS, twelve of them are new compounds, and two others are already known for the species. The PEE, quercitrin and myricitrin promoted a concentration-dependent inhibition of TNF-α, and PEE promoted an inhibition of NF-κB pathway. Conclusions: PEE from C. lineatifolia leaves demonstrated significant anti-inflammatory activity that may be related to the traditional use to treat gastrointestinal disorders. Graphical abstract: Image 1 Highlights: C. lineatifolia is a medicinal plant often used for gastrointestinal disorders. Twelve new compounds were identified for the first time in the species. Phenolic-rich extract and isolated flavonols exhibited anti-inflammatory activity. Antiulcer mechanism may be associated with inhibition of the NF-κB/TNF-α pathway.